John L. McCrea papers - McCrea, John L. (John Livingstone), 1891-1990.
Correspondence, speeches, subject files, clippings, photographs, and other papers pertaining to McCrea's career in the U.S. Navy. Subjects include his appointment as executive officer of the United States Naval Station, Guam, and his service as commander of the USS Iowa. Correspondents include Ray J. DeBurgh and Hugh Rodman.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Naval officer and insurance executive.
Collection material in English.
Keywords: DeBurgh, Ray J. -- Correspondence; Rodman, Hugh, -- 1859-1940 -- Correspondence; United States. -- Navy; United States. -- Navy -- Foreign service -- Guam; Iowa (Ship); United States Naval Station (Guam); Insurance executives; Naval officers